PERANCANGAN PLAZA LAMONGAN DENGAN TEMA ARSITEKTUR NEO VERNAKULAR - Qahar, Dhiah Agustina; Tiyo Rifky, Moh. Agus (DEARSIP : Journal of Architecture and Civil, 2023)
Plaza is a certain area consisting of one or several shops that are erected vertically or horizontally in a city, which are sold or leased to business actors or managed independently to conduct goods trading activities. The use of neo vernacular architectural themes aims to preserve local elements formed empirically by a tradition which then more or less undergoes renewal towards a more modern or advanced work without putting aside local traditional values. Buildings that are more varied, flexible, innovative, dynamic and diverse, both in material and technology are able to achieve visual targets, rooms and outdoor spaces that achieve harmony in the Plaza design. And also this concept in principle pays attention to normative, cosmological principles, the role and local culture in people’s lives and the harmony between buildings, nature and the environment. The whole building has 3 zoning, namely the private zone, the semi-public zone, and the public zone.